Effects of Plasticizer and Cinnamon Essential Oil Incorporation on Mechanical and Water Barrier Properties of Semirefined Iota-Carrageenan-based Edible Film. Issue 1 (July 2021) - Praseptiangga, D; Rahmawati, A; Manuhara, G J; Khasanah, L U; Utami, R
Abstract: Iota-carrageenan, a water-soluble polymer extracted from red seaweed, Eucheuma denticulatum, showed a high potentiality as a film-forming material. Whilst, one of the essential oils that gained increasing attention is from cinnamon because of its recently observed antimicrobial and antioxidant properties. In this study, mechanical and water barrier properties of semi-refined iota-carrageenan (SRiC)-based edible film incorporated with cinnamon essential oil were evaluated into two stages. Firstly, the effects of sorbitol plasticizer's concentration (0.5%, 1.0%, 1.5% v/v) on the mechanical and water barrier properties of the SRiC-based edible film (2% w/v) was investigated, and secondly, those of cinnamon essential oil's incorporation (0.5%, 0.75%, and 1.0% v/v) were evaluated. SRiC (2% w/v) produced with 0.5% (v/v) sorbitol plasticizer addition was selected for the first stage, and 1% (v/v) cinnamon essential oil incorporation on SRiC-based edible film was recommended for the second, suggesting its further utilization in food application.